A Training in Making Technology Innovation Proposals for Students of SMA Negeri 1 Salatiga - Santika, Maria Enggar; Ardian Febrianto , Andreas; Satrio Wicaksono, Bagus; Surya Pranata, Sirilus Widi (Politeknik Negeri Jember, 2024)
In today's advances in science and technology, students have a vital role in becoming users and developers of the technology itself. Critical and innovative thinking skills are needed to support the rapid development of technology. So, the aim of holding this activity in the form of training in making innovative work proposals is to help provide knowledge about the stages of writing scientific papers to improve these abilities. Students can be motivated to think critically through this training activity; apart from that, it can encourage them to participate more actively in writing scientific papers as a means of self-development and to prepare them to continue their education to the next level. From the results of training activities carried out at SMA Negeri 1 Salatiga students were able to create 5 innovative work titles, 2 of which were able to advance to the round of 16 in the Krenova Competition at the Salatiga City level.